Controller Reduction of Parameter Dependent Systems - Widowati, Widowati; Riyanto, Bambang; Saragih, Roberd (Journal of Engineering and Technological Sciences, 2004)
This paper proposes a controller reduction of linear parameter dependent systems. A measure of the degradation is derived for the parameter dependent closed-loop performance caused by applying the reduced-order parameter dependent controller. This measure can be obtained by extending the degradation of the closed-loop performance of the balanced truncation of the corresponding time invariant systems. To verify the performance of the reduced-order controller, an application of the proposed controller reduction method to vertical acceleration of a missile is presented.